Skogsfastigheter i Jämtland : är det en intressant kapitalplacering i jämförelse med aktier? - Norman, Karl-Olof (SLU/School for Forest Management, 2008)
Forest as an investment alternative has become more and more popular over the last few years. Between the years 2004 and 2007 increased the price level on forest land with 70 percent in Jämtland. In this thesis a comparison has been conducted between forest in Jämtland and an investment in the stock market. The risk in the two investment alternatives has been included in the comparison. The thesis includes two different studies between the two alternatives. One historical study from 1986- 2006 also a future comparison has been conducted from 2007 and forward. The historical study shows that the stock market has been a better investment alternative between the years 1986-2006. The forest has had a lower risk measured as standard deviation. Even thou the risk has been lower for the forest does it not compensate the lower level of yield compared to the stock market. An interesting discovery is that the stock market sometimes is the opposite of the forest in few periods. In a period when the forest is going down the stock market is going up. The same connection is observed when the forest is on its way up the stock market is going down. In the future study its hard to tell correct conclusions because it does not exist two similar methods in comparing the stock and forest markets yields in the future. The historical study tends to be similar to the future study. The stock market is probably a better investment alternative compared to the forest in spite that the risk is included. An important item to declare is that only the economical aspects are included in this study between the two investment alternatives. For example have not hunting values and the positive feeling of owning forest been taken to account. Probably are these non monetary values the explanation to why people are buying forest in spite it is not an economical rationally correct decision.